Pengembangan E-Modul Pengenalan Data Statistika Menggunakan Konteks Budaya Melayu Lelang Tembak - Sujinal Arifin; Arvin Efriani; Dwi Rika Amalia Putri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2023)
This study aims to produce an e-module on statistics using the Malay cultural context of shooting auctions that is valid and practical and has a potential effect on students' problem-solving abilities. This research is a development research with the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The subjects in this study were students of class VIII SMP Negeri 50 Palembang. Research data collection was carried out using validation questionnaires, practicality questionnaires, and tests. Validity data was obtained by validating the e-module by 2 validators, and practicality data was obtained through a practicality questionnaire given to students. While the potential effect is seen based on evaluation through problem solving ability test questions. The results showed that the validity score was 0.77 in the moderate validity category, the practicality percentage was 83.52% in the very practical category and the potential effect value on students' problem-solving abilities achieved a completeness score of 88% in the